Memory and Ukuzilanda - Mpuma, Nondwe (Multilingual Margins: A journal of multilingualism from the periphery, 2024)
Background: The concept, better yet the word ukuzilanda comprises several meanings and must be understood as a word in two parts, “landa” as being the lexical item and “ukuzi” as a combined prefix. This understanding is by no means grammatically correct or posing as though it is from a linguist. By combined prefix, I mean that “ukuzi” can be broken down further to “uku” and “zi”; one indicating the act of doing and the other indicating an individual subject respectively.